Explanatory model of depression and anxiety as predictors of suicidal ideation in Peruvian adults - Jonatan Baños Chaparro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: Depressive and anxiety symptoms are frequent emotional disorders in general population adults. The comorbidity of both groups of symptoms considerably affects health, and the literature refers that they are risk factors for the development of suicidal ideation. Objective: Evaluate an explanatory model of depression and anxiety as suicidal ideation predictors in Peruvian adults. Methods: a descriptive, cross-sectional study with a predictive design, with a sample of 566 Peruvian adults who agreed to answer self-report measures on depression, anxiety and suicidal ideation. A structural equation model was performed to evaluate the explanatory model. The Patient Health Questionnaire-2, the Generalized Anxiety Disorder-2, and the Suicidal Ideation Frequency Inventory were applied. To assess the fit of the model, structural equation modeling and a robust weighted least squares estimator adjusted for mean and variance were used. Results: depression (β = 0.52, p = 0.01) and anxiety (β = 0.23, p = 0.03) predict suicidal ideation in a statistically significant way. The proposed model presented adequate values in terms of comparative fit index (0.97), mean square error of approximation (0.03) [90% CI: 0.01-0.05] and standardized mean square error (0.02). Conclusion: Symptoms of depression and anxiety predict the development of suicidal ideation. The evaluation and monitoring of both could help reduce the risk of suicidal ideation, especially when there is comorbidity.